Photoprotective and multifunctional polymer film with excellent near-infrared and UV shielding properties. (December 2020) - Yuan, Hao; Li, Ting; Wang, Yang; Ma, Piming; Du, Mingliang; Liu, Tianxi; Yan, Yangyang; Bai, Huiyu; Chen, Mingqing; Dong, Weifu
Abstract: Polymeric optical composites have played an important role in selectively shielding solar light to satisfy the increasing requirements of photoprotection and environmental comfort as well as improving the energy saving efficiency of buildings and cars. In the present work, a smart polymer film with high near-infrared (NIR) and ultraviolet (UV) light shielding, acceptable visible light transmittance was developed on basis of CuS nanoplate. The influences of the CuS nanoplate size and the thickness of polymer composite films on the optical and shielding properties were studied. In particular, the composite film can shield 86.5% of the near-infrared light from 800 to 1800 nm and at the same time permitting acceptable visible light (63.4%) with the film thickness of 30 μm. In order to improved UV-shielding performance, CuS nanoplate coated by polydopamine (PDA) was used for preparation of polymer composite film. It was found that UV-shielding performance was further promoted in the entire UV region and exhibited a synergistic relationship between PDA and CuS, which certificating the outstanding contribution of PDA layer on the surface of CuS nanoplate. In a word, the comprehensive research on nanocomposite fabrication, surface modification, and integration techniques enable us to fabricate highly flexible, transparent and reliable composite films with outstanding UV and NIR shielding performance. This novel film is potential to be used as smart windows of buildings and cars for the application of cooling energy saving and UV protection. Graphical abstract: Image 1 Highlights: CuS nanoplates with different size were successfully synthesized and their optical property was investigated. CuS nanoplate was coated with polydopamine to further enhance its UV shielding performance. Excellent NIR and UV shielding composite film with a high optical transparency. Simple syntheses process indicate the promising prospect in industry production.